Technological Determinism and Diffusion of Innovation Theories: A Conceptual Analysis Using Apple Products and Immunization among Health Practitioners in Nigeria - Mojolaoluwa Yeri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2026)
The advancement of technology continues to reshape global societies, as it influences the way we communicate, modern systems of the economy, and public health practices. This conceptual paper examines Technological Determinism and Diffusion of Innovations with a use case of Apple products as an example of end user equipment and immunization adaptation among health practitioners in Nigeria as public health advancement. The analysis argues that while Technological Determinism provides insight into how digital tools and biomedical technologies reconfigure professional routines and healthcare delivery, it risks overstating the autonomous power of technology. Diffusion of Innovation theory offers a more socially embedded explanation, highlighting communication channels, opinion leaders, and organizational support systems as critical determinants of adoption. By juxtaposing consumer technology adoption with immunization practices, the paper demonstrates that innovation uptake in Nigeria’s health sector cannot be understood solely through technological capability; rather, it emerges from a dynamic interaction between technology, social structure, policy environment, and professional identity. Even though Technological Determinism argues that technology drives social transformation, Diffusion of Innovation Theory also emphasizes social systems, information sharing mechanisms, and institutional structures and frameworks. By including Nigerian discussion settings in the term paper, allows easy identification of theoretical gaps and recommends an integrated framework that permits both technological framework and cross-cultural societal communication. This review points that innovation adoption in Nigeria is shaped not only by technological availability but also by trust, institutional strength, cultural beliefs, and economic realities.